The Amanhecer case study: applying business intelligence to the wholesaler-retailer relationship - Silva, Rita Castelbranco da Silveira Coelho (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence